ON THE PSYCHOLOGICAL FOUNDATIONS OF ECONOMIC DEVELOPMENT - ODEDOYIN, Stephen Olabode (Theoretical and Practical Research in Economic Fields; Vol 10 No 1 (2019): TPREF, Volume X, Issue 1(19), Summer 2019, 2019)
This paper considered theoretical propositions on the psychological mechanism underlying economic growth and development in diverse nations, particularly how it accounts for variations in levels of per capita income across the globe. Descriptive and analytical techniques were employed in eliciting the basic parameters that underlie this psychological mechanism which motivates inevitably productive economic engagements in various countries of the world. Though the paper appeared to hypothesize a sort of psychological model of economic growth and development, it is merely an attempt in accounting for the growth and development experiences of diverse nations across the world from the theoretical standpoint of their underlying psychological considerations.